KENDALA PEMBELAJARAN DARING PADA PERKULIAHAN MATEMATIKA DASAR MAHASISWA STIT AL-HILAL SIGLI - Junaidah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study analyzes the constraints of online learning in elementary mathematics lectures of STIT Al-Hilal Sigli students. The purpose of this study was to determine the constraints of online learning in basic mathematics courses and to determine the causes. As for the samples in this study were students of PAI study program and semester II PBA study program who were taking basic mathematics courses totaling 51 students. The data collection technique was carried out by distributing questionnaires to students online through the Google form application. The data analysis technique was carried out by descriptive analysis of the constraints of online learning in basic mathematics courses and the factors causing them. The results of the study found several obstacles in online lectures, including: (1) respondents generally live in rural areas so that the quality of the internet network is not adequate, (2) online learning consumes a lot of internet quota, (3) constraints from a financial perspective, (4) gets interrupted from the family during the online learning process, (5) the respondents were busy with other activities during the lecture. The factors that cause obstruction of online learning are: Internal factors include: (1) Respondents' lack of interest in mathematics, (2) Motivation to learn in online learning is still lacking, (3) Respondents often forget about class schedules. External factors include: (1) economic factors, (2) family factors, and (3) inadequate internet network.